Diagnostic criteria for erosive lichen planus affecting the vulva: an international electronic‐Delphi consensus exercise. (13th August 2013) - Simpson, R.C.; Thomas, K.S.; Leighton, P.; Murphy, R.
Summary Background There is no defined set of criteria for diagnosing erosive lichen planus affecting the vulva (ELPV) and there is geographical variation in management. Objectives To reach consensus on clinicopathological diagnostic criteria for ELPV. Methods This was a three‐stage international electronic‐Delphi exercise with a subsequent formal feedback process. In the first two rounds participants were asked to rate the importance of a list of clinicopathological criteria. Responses from round 1 were summarized and presented in round 2, along with additional criteria suggested by participants. In round 3, participants were asked to rate the items that had reached consensus as 'essential' or 'supportive' features in diagnosing ELPV. Consensus was defined as being reached if 75% of participants agreed on the importance of an item. Results A total of 73 experts representing dermatology, gynaecology, histopathology and genitourinary medicine participated; 69 (95%) completed all three rounds. Consensus was achieved for the following 'supportive' diagnostic criteria: (i) well‐demarcated erosions/erythematous areas at the vaginal introitus; (ii) presence of a hyperkeratotic border to lesions and/or Wickham striae in surrounding skin; (iii) symptoms of pain/burning; (iv) scarring/loss of normal architecture; (v) presence of vaginal inflammation; (vi) involvement of other mucosal surfaces; (vii) presence of a well‐defined inflammatory band involving the dermoepidermo junction; (viii) presence of an inflammatory band consisting predominantly of lymphocytes; and (ix) signs of basal layer degeneration. It was suggested that at least three supportive features should be present to make a diagnosis of ELPV, although this number is subject to further discussion. Conclusions This study has identified a diagnostic dataset for ELPV that can be adopted into clinical practice and clinical trials.